2021
DOI: 10.3390/fermentation7010014
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Human Gut Microbiota Inoculums for In Vitro Fermentations Studies

Abstract: The use of fecal inoculums for in vitro fermentation models requires a viable gut microbiota, capable of fermenting the unabsorbed nutrients. Fresh samples from human donors are used; however, the availability of fresh fecal inoculum and its inherent variability is often a problem. This study aimed to optimize a method of preserving pooled human fecal samples for in vitro fermentation studies. Different conditions and times of storage at −20 °C were tested. In vitro fermentation experiments were carried out fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 56 publications
2
28
1
Order By: Relevance
“…In this study, the aerobic as well as anaerobic cell count reached the same level as before the freeze-drying preservation step. This may be due to different cultivation conditions in the study of Carvalho et al (2021) and this study that resulted in lower cell counts. Further, during freezing, intracellular ice can be formed and the increase in solute concentration imposes osmotic stress to the cell (Santivarangkna et al, 2008).…”
Section: Re-establishment Of An In Vitro System After Dryingmentioning
confidence: 80%
See 1 more Smart Citation
“…In this study, the aerobic as well as anaerobic cell count reached the same level as before the freeze-drying preservation step. This may be due to different cultivation conditions in the study of Carvalho et al (2021) and this study that resulted in lower cell counts. Further, during freezing, intracellular ice can be formed and the increase in solute concentration imposes osmotic stress to the cell (Santivarangkna et al, 2008).…”
Section: Re-establishment Of An In Vitro System After Dryingmentioning
confidence: 80%
“…Compared with other studies, when stool samples were preserved by freezing, the cell count irreversibly dropped about one log CFU ml −1 and could not reach the same level as before preservation (Carvalho et al ., 2021 ). In this study, the aerobic as well as anaerobic cell count reached the same level as before the freeze–drying preservation step.…”
Section: Resultsmentioning
confidence: 99%
“…Biobanked stools stored in the presence of preservation chemicals, such as glycerol, are commonly used for either microbiome assay, fermentation or FMT applications. 13 , 17 , 18 Using the bacterial cell counting approach, Guerin-Danan et al . demonstrated that freezing in glycerol buffer had no effect on aerobes in fecal samples, while decreased the survival of anaerobes, but did not exceed the inter-individual variations.…”
Section: Introductionmentioning
confidence: 99%
“…Biobanked stools stored in the presence of preservation chemicals, such as glycerol, are commonly used for either microbiome assay, fermentation or FMT applications 13, 17, 18 . Using the bacterial cell counting approach, Guerin-Danan et al .…”
Section: Introductionmentioning
confidence: 99%
“…Biobanked stools stored in the presence of preservation chemicals, such as glycerol, are commonly used for either microbiome assay, fermentation or FMT applications 13,17,18 . Using the bacterial cell counting approach, Guerin-Danan et al demonstrated that freezing in glycerol buffer had no effect on aerobes in fecal samples, while decreased the survival of anaerobes, but did not exceed the inter-individual variations 19 .…”
Section: Introductionmentioning
confidence: 99%